The impact of offshore wind turbine foundations on local hydrodynamics and stratification in the Southern North Sea - Erik Hendriks; Kobus Langedock; Luca A. van Duren; Jan Vanaverbeke; Wieter Boone; Karline Soetaert; Karline Soetaert (Frontiers in Marine Science)
The development of offshore wind farms (OWFs) in the North Sea is a crucial component for the transition to renewable energy. However, local hydrodynamics in the vicinity of OWF turbine foundations may be affected due to their interaction with tidal currents. This study investigates the impact of offshore wind turbine foundations on local hydrodynamics and stratification in the southern North Sea. We conducted a series of measurements around a single monopile in the Belgian part of the North Sea, focusing on hydrodynamics, salinity and temperature both near the surface and over the water column, and turbulent kinetic energy (TKE). Our results indicate that the foundation-induced wake significantly affects local hydrodynamics, leading to a well-defined band of colder, more saline water at the surface and warmer, less saline water near the seabed. This is quantified through the Potential Energy Anomaly (PEA), which shows a marked decrease in the wake-affected area. The wake is spatially confined, with a width of approximately 70 meters and a length of less than 400 meters downstream of the monopile. Additionally, our measurements reveal an increase in TKE within the wake, indicating enhanced turbulent mixing. This mixing reduces vertical gradients in salinity and temperature, leading to a more homogeneous water column. The findings highlight the importance of considering monopile-induced mixing in large-scale hydrodynamic and ecosystem models, as these effects can influence nutrient transport, primary production, and overall ecosystem dynamics. Furthermore, our research provides valuable data for validating and improving the models used to predict the ecological impact of OWFs.